Fotobiomodulação em células de pele humana envolvidas no processo de reparo tecidual - Ferreira, Fabiana dos Santos (2020)
Treatment with an LED photobiomodulation is a widely used resource without tissue repair with promising results. However, in cancer physiotherapy, it is more in the prevention of radiodermatitis, the use of the resource is still recent and the results are more precise. Therefore, it is necessary to evaluate and understand the effects that LED photobiomodulation has on the skin cells involved in the tissue repair process. Objective: To verify the effects of light-emitting photobiomodulation on human skin cells involved in the tissue repair process. Methods: This research project is characterized as an in vitro experimental study in which human skin cells, HFF-1 fibroblasts will be exposed to different wavelengths: red LED, 658 nm wavelength and LED blue 470 nm, during monitoring for a maximum of 30 days. The tests to be performed include colorimetric, fluorimetric and microscopic methods of verification of parameters related to cell viability and proliferation and free radical formation. It is believed that the data displayed in this research serve as a scientific scientific reference for further studies, including human clinical trials that are of interest for the future. In addition, it is possible to use as a scientific comparison for clinical practice, where LED photobiomodulation may be a safe, low non-pharmacological alternative for radiodermatitis prevention. Results: The blue light demonstrated potential for cell protection mainly by reducing the formation of free radicals and protecting the cell membrane observed with the reduced number of double-stranded DNA strands. The red light, on the other hand, showed less potential for cell protection, due to the risk of the association between greater formation of nitric oxide with increased formation of reactive oxygen species, in addition to having a greater amount of extracellular DNA. Conclusion: A potential beneficial effect of 18 J/cm² blue light was observed for the prevention of cell injuries such as those that occur in radiodermatitis. Despite the consolidated action of red light in the treatment of wounds, this does not seem to be the best option in prophylaxis. Clinical trials are encouraged so that the benefits seen at the cellular level can prove to be beneficial in preventing radiodermatitis in humans.